Aktivitas Farmakologi Senyawa Aktif yang Diisolasi dari Tumbuhan Obat - Alifia Hasna Hamidah; Tiana Milanda (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Traditional medicine is currently developing rapidly, especially those based on plants. Active plant compounds are the main basis for the development of new drugs, which after further research, can be commercialized and used in pharmaceutical treatment. This review was conducted to identify the pharmacological effects of active drug compounds isolated from medicinal plants by conducting a literature study. The results of the literature review contained 37 articles that met the inclusion criteria. Until now, there are several active drug compounds from plants that are sold commercially in the form of modern drugs. Some of the pharmacological effects found are cardiac glycosides, anticholinergics, antiplatelets, analgesics, anticancer, sympathomimetics and antimalarials. This search shows that natural materials are still used as a potential source of active drug compounds, thus encouraging research to find new active compounds from medicinal plants to overcome diseases in the future.